Characterisation of physicochemical properties, anti-hyperglycaemic effects, and probiotic potentials in fermented pumpkin drink utilising Lactobacillus mali isolated from water kefir - Koh, W. Y; Lim, X. X; Uthumporn, U; Tan, T. C; Kobun, R.; Rasti, B (Universiti Putra Malaysia, 2024)
Pumpkin has been reported to be a good probiotic delivery vehicle, but it has a short shelf life, is susceptible to enzymatic browning, and prone to microbial spoilage. Pumpkin could be transformed into a value-added beverage through the fermentation by LAB. In the present work, the probiotic viability, physicochemical, antioxidative, antihyperglycemic, and sensory properties of Lactobacillus mali-fermented pumpkin drink (FPD) during eight weeks of refrigerated storage at 4°C were investigated. There were significant reductions (p < 0.05) in colour, pH, texture characteristics, and antioxidant properties after four weeks of storage. FPD exhibited total phenolic content ranging from 83.75 to 90.75 mg GAE/mL, total flavonoid content ranging from 47.01 to 50.01 mg QE/mL, FRAP reducing power ranging from 160.76 to 169.76 µmol Trolox equivalent/mL, and DPPH scavenging activity ranging from 52 to 54.56% during storage. FPD's total soluble solids decreased (p < 0.05) from 0.60 to 0.02 °Brix, while concentrations of ethanol (0.62 to 1.2%, v/v), lactic acid (0.03 to 0.11 g/L), and acetic acid (0.02 to 0.18 g/L) significantly increased (p < 0.05) over eight weeks of storage. L. mali strain within FPD maintained its viability (p > 0.05) under simulated gastrointestinal conditions, with 8 - 9.1 log CFU/mL for 28 days at 4°C. FPD retained up to 90% α-glucosidase enzyme inhibition throughout the 28 days storage period. Sensory evaluation showed that FPD's attributes remained unchanged (p > 0.05) during the initial four weeks of storage, with an overall acceptability score ranging from 6.56 to 6.88. In conclusion, FPD remained stable in terms of physicochemical, antioxidative, and sensory properties, as well as probiotic viability and anti-hyperglycaemic effects during 28 days of refrigerated storage. This highlights FPD’s potential as a functional beverage, presenting an innovative method to utilise pumpkin as an effective probiotic carrier.